Pengaruh Pengetahuan Perpajakan, Motivasi Sosial, Dan Motivasi Karir Terhadap Minat Mahasiswa Akuntansi Dalam Mengikuti Pelatihan Brevet Pajak - Muhammad Afdal Usman; Fajar Rina Sejati; Muthmainnah Muthmainnah (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to examine the influence of tax knowledge, social motivation and career motivation on students' interest in participating in tax brevet training. This research is quantitative research by collecting data using survey methods. The sample for this research was 77 accounting students who were actively registered at Yapis University, Papua. Sampling used simple random sampling technique. The results of this research indicate that tax knowledge has a significant effect on interest in participating in tax brevet training. Meanwhile, social motivation and career motivation do not have a significant effect on interest in participating in tax brevet training.